Project-based learning for Arabic instruction as an innovation of the Kurikulum Merdeka development - Yuliasari Yuliasari; Moch. Wahib Dariyadi; Laily Maziyah; Muhammad Alfan (Inovasi Kurikulum, 2025)
This study is grounded in the need for a more contextual and participatory approach to Arabic language instruction that aligns with the characteristics of the Pancasila Student Profile, particularly in non-urban madrasahs. Conventional methods have been deemed insufficient in effectively fostering students' communicative competencies. The objective of this study is to examine the implementation of the Project-Based Learning (PjBL) model in Arabic language education at Madrasah Ibtidaiyah (MI) as part of the ongoing innovation within the Kurikulum Merdeka. A descriptive qualitative method was employed, utilizing participatory observation, in-depth interviews, and document analysis for data collection. The findings reveal that PjBL successfully integrates Arabic language content into real-world activities, such as creating family introduction videos and creating vocabulary posters. This approach significantly enhances students' speaking skills (maharah kalām), collaboration abilities, and self-confidence. Moreover, it promotes a shift in the teacher’s role from instructor to facilitator, supporting differentiated learning practices. Despite challenges related to limited resources and the need for teacher training, PjBL proves to be a flexible and effective strategy for teaching the Arabic language. This study presents a replicable model for enhancing curriculum and developing 21st-century competencies, grounded in Islamic values.   Abstrak Penelitian ini didasarkan pada kebutuhan akan pendekatan pembelajaran bahasa Arab yang lebih kontekstual, partisipatif, dan selaras dengan profil pelajar Pancasila, terutama di madrasah non-perkotaan. Pendekatan konvensional dinilai belum mampu mengembangkan keterampilan komunikasi siswa secara optimal. Penelitian ini bertujuan untuk mengkaji penerapan model pembelajaran berbasis proyek (Project-Based Learning/PjBL) dalam pembelajaran bahasa Arab di Madrasah Ibtidaiyah (MI) sebagai bagian dari inovasi pengembangan Kurikulum Merdeka. Metode yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data berupa observasi partisipatif, wawancara mendalam, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan PjBL mampu mengintegrasikan materi bahasa Arab ke dalam aktivitas nyata seperti video perkenalan keluarga dan pembuatan poster kosa kata. Pendekatan ini secara signifikan meningkatkan keterampilan berbicara (maharah kalām), kemampuan kerja sama, dan rasa percaya diri siswa. Guru juga mengalami pergeseran peran menjadi fasilitator pembelajaran yang mendukung pembelajaran terdiferensiasi. Meskipun terdapat keterbatasan fasilitas dan kebutuhan pelatihan guru, PjBL terbukti sebagai strategi yang fleksibel dan efektif dalam pembelajaran bahasa Arab. Penelitian ini memberikan model inovasi yang dapat direplikasi dalam penguatan kurikulum dan pengembangan kompetensi abad ke-21 berbasis nilai-nilai Islam. Kata Kunci: inovasi kurikulum; literasi bahasa Arab; Kurikulum Merdeka; pembelajaran berbasis proyek